Does a bank's business model affect its capital and profitability?. (29th January 2020) - Farnè, Matteo; Vouldis, Angelos T.
Abstract: We use a data‐driven classification of systemically important European banks into business models based on confidential granular supervisory data and investigate whether banks following different models differ with respect to their capitalisation and profitability. Our aim is to locate the banks' business model in a risk‐return space. Using an instrumental variables approach, our econometric methodology addresses potential endogeneity issues. Overall, we find that wholesale funded and securities holding banks are positioned on a relatively high risk‐return trade‐off plane compared with commercial banks. On the other hand, traditional commercial banks earn lower returns with moderate risk.